Effect of Azospirillum Brasilense, Flavobacterium Spp. biofertilizers and Al Khasieb Organic fertilizer on growth and yield of Sweetpotato (Ipomoea batatas L.) under field conditions - Ahmed, Yassin M.; Hassan, Gadalla A. El; Hadad, M. A.; M. M., Alsamowal (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2016)
A field experiment was conducted in the Experimental Farm of the College of AgriculturalStudies, Sudan University of Science and Technology Shambat to study the effect of inoculation with Azospirillum brasilense, Flavobacterium spp, and Al Khasieb organic fertilizer application rate on growth and yield of sweetpotato (Ipomoea batatas L). Azospirillum brasilense and Flavobacterium spp inoculum were applied at the concentrationof (108Cfu/ml), with three levels of Al Khaseeb organic fertilizer; (0 t/ha, 0.8 t/ha and 1.2t/ha). The experiment was set in factorial arrangement in a randomized complete block design with three replicates. Application of (Azospirillum +1.2 t/ha of Al Khaseeb organicfertilizer) and (Azospirillum + Flavobacterium+ 0.8 t/ha of organic fertilizer) showed significant effect on sweetpotato stem length, Leaf number, branches number after six and sixteen weeks with (107.67cm), (72) and(5); (193cm), (193) and(13) respectively compared to uninoculated control, also application of Azospirillum + Flavobacterium+ 0.8 t/ha of organic fertilizer showed the highest effect on marketable storage roots yield with (13.5 t/ha) compared to (6.71 t/ha)) for the uninoculated control. However, the application of 1.2 t/ha of Al Khaseeb organic fertilizer alone showed lowest values in some parameters. The resultsindicated the great potential of combined application of Azospirillum brasilense, Flavobacterium biofertilizers and Al Khaseeb organic fertilizer in improving growth andyield of sweetpotato under field conditions.